Implications of Professional Codes of Ethics for the Role of Lawyers in the Contemporary Legal System - Ahmad Fatoni; Hj. Yeti Kurniati; Hj. Hernawati RAS (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research examines the impact of the Code of Professional Ethics on lawyers' practice in an ever-changing legal environment. By considering changes in technology, communications, and the contemporary legal environment, this research explores how lawyers interpret and apply codes of ethics in situations involving moral and ethical conflicts. Through in-depth analysis, this research documents how lawyers adapt to the dynamics of the modern legal environment while maintaining ethical integrity in their legal practice